Brazilian public policy for chronic kidney disease prevention: challenges and perspectives - Silva, Patrícia Aparecida Barbosa; Silva, Líliam Barbosa; Santos, Joseph Fabiano Guimarães; Soares, Sônia Maria (Revista de Saúde Pública, 2020)
Chronic kidney disease is a pathology with exponential increasing prevalence worldwide. This trend derives mainly from population aging and the growth of chronic conditions, making prevention a priority in public health. Thus, this observation instigates debates on the advances and challenges in public policies aimed at facing the progression of this disease and its risk factors in a contemporary reality that requires changes in the management models of chronic conditions. Brazilian and international experiences show that actions to prevent chronic kidney disease in risk groups remain incipient, especially in low-income countries. This area requires investment, supporting planning individualized, interdisciplinary and shared care with primary health care, as well as the user’s responsibility for their care, with proactivity and establishment and monitoring of goals to achieve satisfactory results.